Updating spatial working memory in a dynamic visual environment. (October 2019) - Boon, Paul J.; Theeuwes, Jan; Belopolsky, Artem V.
Abstract: The present review describes recent developments regarding the role of the eye movement system in representing spatial information and keeping track of locations of relevant objects. First, we discuss the active vision perspective and why eye movements are considered crucial for perception and attention. The second part focuses on the question of how the oculomotor system is used to represent spatial attentional priority, and the role of the oculomotor system in maintenance of this spatial information. Lastly, we discuss recent findings demonstrating rapid updating of information across saccadic eye movements. We argue that the eye movement system plays a key role in maintaining and rapidly updating spatial information. Furthermore, we suggest that rapid updating emerges primarily to make sure actions are minimally affected by intervening eye movements, allowing us to efficiently interact with the world around us.